Exploring literacy through theatre: The impact of performing on literacy and upgrading students - Cynthia Lee Andruske (Adult Education Research Conference, 1993)
This paper explored the impact performing in the literacy play Marks on Paper had on adult literacy and upgrading students in British Columbia, Canada, from 1989-1992. The findings suggest that through performance learner/actors experienced an increased positive self-image and an increased awareness about illiteracy. Often this translated into a sense of empowerment resulting in transformations in perspectives and actions for the students.